Expression of CD44 on rheumatoid synovial fluid lymphocytes. Issue 7 (July 1995) - Kelleher, D; Murphy, A; Hall, N; Omary, M B; Kearns, G; Long, A; Casey, E B
Abstract : OBJECTIVES–To investigate the involvement of the adhesion molecule CD44 in the homing of lymphocytes to synovial tissue, by examining the density of expression and molecular mass of CD44 on rheumatoid synovial fluid lymphocytes. METHODS–Twenty patients with rheumatoid arthritis were studied. Peripheral blood and synovial fluid lymphocytes were isolated by Ficoll-Hypaque sedimentation. CD44 expression was analysed by two colour flow cytometry of CD3 positive T lymphocytes with calculation of mean fluorescence intensity. Expression of activation markers M21C5, M2B3, interleukin (IL)-2 receptor and transferrin receptor was quantitated. In addition, CD44 molecular mass was examined by Western blot in six patients. RESULTS–CD44 expression was markedly increased on synovial fluid T lymphocytes of rheumatoid patients relative to peripheral blood lymphocytes from the same individuals. CD44 molecular mass on peripheral blood mononuclear cells was 88 kDa, but that on synovial fluid lymphocytes was only 83 kDa. CD44 expression correlated significantly with expression of activation markers M21C5, M2B3, and the IL-2 receptor. CONCLUSIONS–Alterations in density of expression or of the molecular mass of CD44 could contribute to local tissue injury, either directly by facilitating adhesion, or indirectly through effects on other adhesion molecules.